Direct measurement of near‐nano‐Newton forces developed by self‐organizing actomyosin fibers bound α‐catenin. (20th August 2021) - Sonam, Surabhi; Nguyen‐Vigouroux, Clémence; Jégou, Antoine; Romet‐Lemonne, Guillaume; Le Clainche, Christophe; Ladoux, Benoit; Mège, René Marc
Abstract : Background Information: Actin cytoskeleton contractility plays a critical role in morphogenetic processes by generating forces that are then transmitted to cell–cell and cell‐ECM adhesion complexes. In turn, mechanical properties of the environment are sensed and transmitted to the cytoskeleton at cell adhesion sites, influencing cellular processes such as cell migration, differentiation and survival. Anchoring of the actomyosin cytoskeleton to adhesion sites is mediated by adaptor proteins such as talin or α‐catenin that link F‐actin to transmembrane cell adhesion receptors, thereby allowing mechanical coupling between the intracellular and extracellular compartments. Thus, a key issue is to be able to measure the forces generated by actomyosin and transmitted to the adhesion complexes. Approaches developed in cells and those probing single molecule mechanical properties of α‐catenin molecules allowed to identify α‐catenin, an F‐actin binding protein which binds to the cadherin complexes as a major player in cadherin‐based mechanotransduction. However, it is still very difficult to bridge intercellular forces measured at cellular levels and those measured at the single‐molecule level. Results: Here, we applied an intermediate approach allowing reconstruction of the actomyosin‐α‐catenin complex in acellular conditions to probe directly the transmitted forces. For this, we combined micropatterning of purified α‐catenin and spontaneous actomyosin network assembly in the presence of G‐actin and Myosin II with microforce sensor arrays used so far to measure cell‐generated forces. Conclusions: Using this method, we show that self‐organizing actomyosin bundles bound to micrometric α‐catenin patches can apply near‐nano‐Newton forces. Significance: Our results pave the way for future studies on molecular/cellular mechanotransduction and mechanosensing. Abstract : Anchoring of the actomyosin to adhesion complexes allows mechanical coupling between the intracellular and extracellular compartments. It is, thus, a key issue is to measure associated forces. Here, we combined micropatterning of purified α‐catenin and spontaneous actomyosin assembly with microforce sensor arrays to quantify forces developed by α‐catenin‐bound actomyosin bundles. We show that these self‐organized actomyosin apply near‐nano‐Newton forces, paving the way for future studies on molecular/cellular mechanotransduction and mechanosensing.